THE LATENT TRANSFORMATION PROCESS OF THE FREE ACEH MOVEMENT IDEOLOGY AFTER THE PEACE AGREEMENT - Rusli Yusuf, Maimun, Sanusi, TM. Jamil (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Gerakan Aceh Merdeka (GAM), translated as the Free Aceh Movement, was established in 1976 with the aim of separation from the Unitary State of the Republic of Indonesia (NKRI). After more than 30 years of rebellion against the central government, the two sides reconciled in 2005. One of the most important points agreed upon is that Aceh remains within the framework of the Unitary Republic of Indonesia. However, once the peace agreement was completed, former GAM combatants could still promote their ideology and symbols in latent forms in their families, in formal organizations and in the community at large. This research aims to describe in detail and analyze the latent process of the ideological transformation of the Free Aceh Movement conducted by former GAM combatants through their families, formal institutions or the social environment in general. The results of the study indicate that a latent separatist ideology is still being promoted by former GAM members, both in Aceh and abroad. At the family level, GAM members do not allow their family members to use the Indonesian language or respect the red-and-white Indonesian flag and urge their family members to read books written by Hasan Tiro about Aceh independence and to hold former GAM leaders in high regard. The findings also show that the Milad GAM ceremony is still held every 4th of December in two separate regions, the northeastern coastal region and the southwestern region. From this research, it can be concluded that since the peace agreement, the promotion of GAM symbols and ideology has been an iceberg phenomenon: only a small part is visible on the surface, but the roots are very deep and have a negative impact on the sustainability of Aceh’s peace within the framework of the Unitary state of the Republic of Indonesia.